Role of pattern and multifocal electroretinogram for macular evaluation in patients with multiple sclerosis treated with fingolimod - Randa H. Abdelgawad; Yasmine Z. Abdel Wadood; Mohamed Y.S. Seif; Mahmoud A. Sultan; Dina A. Zamzam; Safaa A.M. Aboud (Journal of the Egyptian Ophthalmological Society)
Objective To detect the role of pattern electroretinogram (PERG) and multifocal electroretinogram (MfERG) for macular function evaluation in patients with relapsing–remitting multiple sclerosis (RR-MS) treated by fingolimod. Patients and methods This prospective research was carried out on 25 patients with RR-MS (50 eyes), treated by fingolimod, with no ophthalmic disorders or complaints before the onset of the treatment, including no history of optic neuritis. PERG, MfERG, and spectral domain optical coherence tomography were performed before then 3 and 6 months after the treatment. Results Best-corrected visual acuity (BCVA) significantly decreased in third and sixth months compared to baseline (P<0.001). Central macular thickness showed nonsignificant change. PERG waveform abnormalities were detected in 2.5% of patients at third month (P=0.9) and 27.5% in sixth month (P<0.001). PERG P50 amplitude nonsignificantly decreased in third month (P=0.6), then significantly decreased at sixth month (P=0.021). PERG N95 amplitude showed no significant difference (P=0.345). MfERG revealed nonsignificant decrease of P1 amplitude of all five rings at third and sixth months. The duration of MS had significant negative correlations with BCVA, amplitude, and amplitude change of P1 of both ring 1 and ring 2. Conclusion Treatment with fingolimod for 6 months led to a significant reduction in BCVA and PERG responses and a slight decrease in P1 amplitude of MfERG before detection of any structural macular changes by optical coherence tomography. This indicates the role of PERG and MfERG as biomarkers for the early detection of macular function alteration in RR-MS fingolimod-treated cases.